Capacity-building during public health emergencies: perceived usefulness and cost savings of an online training on SARS-CoV-2 real-time polymerase chain reaction (qPCR) diagnostics in low- and middle-income settings during the COVID-19 pandemic - Weishaar, Heide; Pozo-Martin, Francisco; Geurts, Brogan; Lopez de Abechuco, Estibaliz; Montt-Maray, Eloisa; Cristea, Florin; Abrokwa, Seth Kofi; Bahr, Thurid; Al-Awlaqi, Sameh; El Bcheraoui, Charbel (Frontiers in Public Health, 2024)
Introduction: Upon the onset of the COVID-19 pandemic, the Public Health Laboratory Support Unit (ZIG4) at the Robert Koch Institute (RKI), the German National Public Health Institute, developed and delivered an online training on SARS-COV-2 qPCR diagnostics to 17 partner countries in low- and middle-income countries (LMIC). This article analyses the usefulness and cost savings of this training. Methods: The authors performed a concurrent mixed-methodology study based on key informant interviews, interviewer-administered questionnaires, and document reviews. Economic costs were estimated from the perspective of RKI. Results: Responding participants indicated that the course provided good and comprehensive information on up-to-date scientific knowledge and laboratory practice in PCR diagnostics. Respondents appreciated how the technical content of the training enhanced their ability to apply diagnostic methods in their daily work. Interviewees highlighted that the fast implementation and the low threshold of attending an online training had allowed them to quickly build skills that were crucial during, and beyond, the COVID-19 crisis. The total estimated cost of the online SARS-CoV-2 qPCR training was 61,644 euros. The total estimated cost of the equivalent face-to-face training was estimated at 267,592 euros. Programme weaknesses identified included the top-down approaches taken, lack of interactive components and opportunities to directly engage with other course participants and with teachers. Conclusions: An online training was developed and implemented to support RKI partner countries in SARS-CoV-2 qPCR diagnostics during the COVID-19 pandemic, thereby strengthening pandemic response and health system resilience. The training incurred in important cost savings compared to the equivalent face-to-face training. Post-pandemic studies could usefully build on these research findings and explore ways to enhance end user involvement and improve interactive features to build stronger communities of learners and facilitate exchange of information and mutual learning.